1975
DOI: 10.1161/01.cir.51.5.761
|View full text |Cite
|
Sign up to set email alerts
|

Role of the slow current in cardiac electrophysiology.

Abstract: MayAN OFFICIAL JOlURNAL ofthe AMERICAN JEART ASSOCIATION NO. 5 1975 EDITORIALRole of the Slow Current in Cardiac Electrophysiology OVER THE PAST TEN YEARS, the concept has emerged that the ionic currents underlying the cardiac action potential include calcium as well as sodium and potassium. The purpose of this communication is to review the development of this concept and attempt to relate it to our understanding of clinical electrophysiology and the pathogenesis of certain arrhythmias. Basic Electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(12 citation statements)
references
References 49 publications
(10 reference statements)
1
8
0
3
Order By: Relevance
“…3) The maximum diastolic potential and the maximum rate of rise of the slow-type AAPs was -54.5 mV and 2.7 V/s, respectively, which agree well with those of the "slow response" with abnormal automaticity (ZIPES et al, 1975). These findings support the notion that activation of 'Ca contributes to the pacemaker potential of the slow-type AAPs.…”
Section: Discussionsupporting
confidence: 78%
“…3) The maximum diastolic potential and the maximum rate of rise of the slow-type AAPs was -54.5 mV and 2.7 V/s, respectively, which agree well with those of the "slow response" with abnormal automaticity (ZIPES et al, 1975). These findings support the notion that activation of 'Ca contributes to the pacemaker potential of the slow-type AAPs.…”
Section: Discussionsupporting
confidence: 78%
“…The initiation of an onset of triggered activity is thus a cycle length-dependent phenomenon. Nevertheless, shortening of the basic driving cycle length may induce unidirectional block in one pathway and slow conduction in the other pathway, setting up conditions for reentry to occur (13,15,20 suggested that the slow channel action potentials may become dominant under pathologic conditions, such as myocardial ischemia, in regions of the heart ordinarily dominated by the fast sodium channel response (39,40). Such slow channel action potentials have been implicated in the genesis of reentrant ventricular arrhythmias because of their propensity for very slow propagation of impulses (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that the calcium-dependent slow channel response may become dominant, and, in turn, may give rise to an automatic rhythm under pathologic conditions (39,40). In this situation, verapamil would be expected to be effective in suppressing such an automatic rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…n u r d e r l a n g s a m e C a l c i u m k a n a l e x i s t i e r t u n d o b e i n s c h n e l l e r N a t r i u m k ahal fehlt o d e r n u r i n a k t i v ist (41,42,43,44,45,46,47). A r t i f i z i e l l e F r e q u e n zs t e i g e r u n g b r e m s…”
Section: B E I D I E S E N Z E L L E N S I N D C a L C I U M I O N E unclassified